Franchising Microfinance - Bubna, Amit; Chowdhry, Bhagwan (Review of Finance, 2010)
Abstract Financial intermediaries worldwide are seeking mechanisms for participating in micro lending. Using informed “local capitalists” as bank's on-lenders fails due to borrowers' incentive to default with multiple credit sources. A coalition of local capitalists may not resolve the problem in the presence of a monopoly moneylender with superior skills in lending and enforcement. A credible competitive threat to the moneylender can only arise if the local capitalist coalition also provides information sharing benefits that lower their cost of lending vis-à-vis the moneylender. Franchising allows local capitalists to form such a coalition. We analyze conditions under which welfare-enhancing franchising would obtain.